Pengaruh Aplikasi Pembelajaran Digital Duolingo terhadap Hasil Belajar Bahasa Inggris Siswa Sekolah Dasar - Faikotus Silvi; Rahma Dwi Lestari; Visca Najwah Arini; Alya Dwi Nur Afifa; Risma Ayu Diya Fitaloka; Alzena Callista Dzahab; Muhammad Lutfi; Agung Nugroho Puspito (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2026)
The main challenges in teaching English at the elementary school level are low motivation and a lack of interactive learning tools, particularly among students at Klabang Agung Elementary School. This study aims to introduce and investigate the use of the Duolingo digital learning app as a support tool in the English teaching process for elementary school students. A quantitative approach with a pretest-posttest design was applied, in which students took an initial test to assess their basic skills before using the app, followed by a final test after the learning period with Duolingo. The findings indicate a significant improvement in students’ average scores, rising from 51.2 on the pretest to 75.4 on the posttest, representing an increase of 49.6%. Additionally, gamification features, interactive exercises, and immediate feedback create an enjoyable learning experience tailored to students’ abilities. This study concludes that the Duolingo app as a digital learning tool is an innovative and effective alternative in supporting English language teaching in elementary schools, particularly in enhancing student motivation and learning outcomes in a sustainable manner.